Distribution of subglacial sediments across the Wilkes Subglacial Basin, East Antarctica. Issue 4 (29th April 2016) - Frederick, Bruce C.; Young, Duncan A.; Blankenship, Donald D.; Richter, Thomas G.; Kempf, Scott D.; Ferraccioli, Fausto; Siegert, Martin J.
Abstract: Topography, sediment distribution, and heat flux are all key boundary conditions governing the dynamics of the East Antarctic Ice Sheet (EAIS). EAIS stability is most at risk in Wilkes Land across vast expanses of marine‐based catchments including the 1400 km × 600 km expanse of the Wilkes Subglacial Basin (WSB) region. Data from a recent regional aerogeophysical survey (Investigating the Cryospheric Evolution of the Central Antarctic Plate (ICECAP)/IceBridge) are combined with two historical surveys (Wilkes basin/Transantarctic Mountains System Exploration‐Ice‐house Earth: Stability or DYNamism? (WISE‐ISODYN) and Wilkes Land Transect (WLK)) to improve our understanding of the vast subglacial sedimentary basins impacting WSB ice flow and geomorphology across geologic time. Analyzing a combination of gravity, magnetic and ice‐penetrating radar data, we present the first detailed subglacial sedimentary basin model for the WSB that defines distinct northern and southern subbasin isopachs with average sedimentary basin thicknesses of 1144 m ± 179 m and 1623 m ± 254 m, respectively. Notably, more substantial southern subbasin sedimentary deposition in the WSB interior supports a regional Wilkes Land hypothesis that basin‐scale ice flow and associated glacial erosion is dictated by tectonic basement structure and the inherited geomorphology of preglacial fluvial networks. Orbital, temperate/polythermal glacial cycles emanating from adjacent alpine highlands during the early Miocene to late Oligocene likely preserved critical paleoclimatic data in subglacial sedimentary strata. Substantially thinner northern WSB subglacial sedimentary deposits are generally restricted to fault‐controlled, channelized basins leading to prominent outlet glacier catchments suggesting a more dynamic EAIS during the Pliocene. Key Points: Wilkes Subglacial Basin (WSB) sedimentary basins are characterized for the first time North and south WSB sedimentary subbasin distribution and isopachs are significantly dissimilar Variation in WSB subglacial sediment distribution and character suggests disparate glacial history